Project development for older adults: orientation's contribution - Gavilán de Labourdette, Mirta Graciela (2010)
This paper systematizes the work developed during the first year of the initiation scholarship for the research project entitled 'Orientation within the new Active Aging Model: educational, work-related, personal and social choices'. This project articulates the Active Aging Model and the Theoretical Operative Model in Orientation, in order to learn how new projects are developed by older adults who used to be part of the formal system of labor and by those who were out of it, and to design programmatic proposals for educational, work-related, personal and social Orientation choices for such population. The sample is made up by seventy people between 64 and 74 years of age, residing in La Plata. The first conclusions evidence the importance that older adults place on project development at this stage of their life cycle, giving special importance to educational, personal and social projects; as well as on the identification of economic factors, health state, family needs for care and social support, among other things, as conditioning the fulfillment of such projects. The differences found in terms of the labor system they used to belong to can be especially observed in the type of project developed.